2012
DOI: 10.3892/ijmm.2012.1035
|View full text |Cite
|
Sign up to set email alerts
|

Effects on inflammatory responses by the sphingoid base 4,8-sphingadienine

Abstract: Abstract. Sphingolipids (SLs) are a class of lipids, which are structural cell components involved in the regulation of cellular processes such as cell proliferation, differentiation, apoptosis and inflammation. Dietary SLs are enzymatically hydrolyzed in the gut lumen into metabolites, namely ceramides and sphingoid bases. The sphingoid base 4,8-sphingadienine (4,8-SD) is the metabolite of glucocerebrosides derived from plants that are part of the human diet. The present findings provide insight into the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…We have shown previously that SDs are cytotoxic to colon cancer cells but not normal intestinal epithelial cells and reduce tumorigenicity in the Apc Min/+ mouse model of colon cancer (24,33). Dietary SDs are antiinflammatory lipids that are taken up by the gut but are poorly absorbed, making them well suited as colon cancer chemoprevention agents (46,47). SDs derived from soy and other nonmammalian dietary sources cannot be metabolized to S1P and are not readily incorporated into mammalian sphingolipids (46).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that SDs are cytotoxic to colon cancer cells but not normal intestinal epithelial cells and reduce tumorigenicity in the Apc Min/+ mouse model of colon cancer (24,33). Dietary SDs are antiinflammatory lipids that are taken up by the gut but are poorly absorbed, making them well suited as colon cancer chemoprevention agents (46,47). SDs derived from soy and other nonmammalian dietary sources cannot be metabolized to S1P and are not readily incorporated into mammalian sphingolipids (46).…”
Section: Discussionmentioning
confidence: 99%
“…In human cells and cell lines, sphingosine is cytotoxic for DLD-1 cells (LD 50 , 26.7 μM) (Sugawara et al, 2006), WiDr cells (LD 50 , 22.9 μM) (Sugawara et al, 2006), Caco-2 colon cancer cells (LD 50 , 24.2 uM) (Sugawara et al, 2006) and HL-60 human promyelocytic leukemia cells (10 μM) (Johnson et al, 2004). 4,8-sphingadienine is cytotoxic for immortalized human umbilical vein endothelial cells (>20.0 μM) (Rozema et al, 2012). In the present study SCC15, SCC19, SCC84, SCC99, and SCC1483 used as controls, were susceptible to sphingosine (range <10.0 to 32.3 μM), dihydrosphingosine (range 5.8 to 28.2 μM), and phytosphingosine (range 7.3 to 17.2 μM) suggesting a potential therapeutic use for long-chain bases against oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Within physiologic concentrations (4.0 -13.2 µg/ml for total fatty acids and 0.5 -5.0 µg/ml for sphingoid bases (Brasser et al 2011a, Brasser et al 2011b), salivary lipids exhibit potent antimicrobial activity against a variety of oral bacteria without apparent harm to eukaryotic cells of the oral mucosa. However our lab recently showed that while sphingoid bases are nontoxic to DCs at low concentrations they are extremely toxic to These results are similar to other studies showing dose-dependent cytotoxicity of sphingosine and other sphingoid base derivatives against immortalized human endothelial cells (HUVECtert cells) (Rozema et al 2012), human epidermoid carcinoma KB cells (Shirahama et al 1997), murine P388 myeloid leukemia cells (Klostergaard et al 1998), and murine B16 melanoma cells (Rives et al 2011). However, little is known about the effects of sphingoid bases on normal (e.g.…”
Section: Discussionsupporting
confidence: 84%